Red Kit : Nazlı Leydi - Barbera, Joseph, 1911-2006 (France France Regions 3, 1990)
An animated series based on the European comic book about an American cowboy described as ""The man who shoots faster than his shadow."" Lucky Luke, with his horse Double Six, travels the Old West to right wrongs and bring evildoers (usually his traditional enemies the Dalton Brothers) to justice.
An animated series based on the European comic book about an American cowboy described as ""The man who shoots faster than his shadow."" Lucky Luke...
Morris
Language(s): Turkish Subtitle(s): No Subtitle
Keywords: Family; Western; Animation